HEAT TREATMENT PADA MATA PISAU ALAT PENGHANCUR ARANG BIOMASA UNTUK MENINGKATKAN NILAI KEKERASAAN DENGAN VARIASI TEMPERATUR - Agustinus Otu; Jack C.A. Pah; Jahirwan Ut Jasron (Universitas Nusa Cendana, 2025)
. This is evidenced by the large use of steel in various machine components, work materials and building construction, both in the form of plates, sheets, pipes and so on. Damage that often occurs in the application of ST 41 steel is wear. Wear occurs due to the influence of external forces in the form of friction and is the most dominant factor in damage to the function of machinery. As a result, the service life and performance of various machine components are reduced and indirectly will increase maintenance costs. The public demand for this metal hardening technology is increasing, so researchers have tried to apply knowledge about metal hardening to knives with low carbon steel materials. Heat treatment aims to increase ductility.. This study shows that Heat Treatment with different temperatures and different cooling media can significantly affect the hardness of low carbon steel. The results of the study showed that the highest hardness of low carbon steel was obtained at a temperature of 950°C with oil cooling media, which was 44.30 HRC.